MULTIKULTURALISME DALAM NOVEL KUSUT KARYA ISMET FANANY - Rulita Marinda; Bakhtaruddin Nasution; Zulfadhli Zulfadhli (Jurnal Bahasa dan Sastra, 2014)
This article to desrcibe multiculturalism in the novel Kusut author by Ismet Fanany. To get the purpose use the study of kualitative with descriptive analyst method. A data of this study is the data multiculturalism solidarityandbrotherhood, open trading, family values, respect for ethics, was enough in life,  and sharing and control of power gainedfromthe studyobjectordata source, that is novel Kusut author by Ismet Fanany.